OP0344 Frame study: the foundation effect of rebuilding bone with one year of romosozumab leads to continued lower fracture risk after transition to denosumab - Cosman, F.; Crittenden, D.B.; Ferrari, S.; Khan, A.; Lane, N.E.; Lippuner, K.; Matsumoto, T.; Milmont, C.E.; Libanati, C.; Grauer, A. (Annals of the rheumatic diseases, 2018)
ObjectivesRomosozumab (Romo), a sclerostin antibody, has a dual effect of increasing bone formation and decreasing bone resorption. In the FRAME study (NCT01575834), one year of Romo treatment resulted in large bone mineral density (BMD) increases at the lumbar spine (LS) and total hip (TH) versus placebo (Pbo).1 The differences between groups remained after all subjects transitioned to denosumab (DMAb) during the second year of study. Here, we further characterise the BMD gains seen during the FRAME study and examine the effect of building bone with Romo on fracture-risk reduction after transition to DMAb.MethodsSubjects in FRAME were randomised to receive monthly Romo 210 mg or Pbo for 12 months, after which all subjects received 6-monthly DMAb 60 mg for an additional 12 months. Endpoints for the current analysis were mean change from baseline in BMD T-score, percentage of subjects with a BMD gain, and fracture incidence in the second year of the FRAME study, including new vertebral, clinical (nonvertebral and symptomatic vertebral), and other fracture categories.Abstract OP0344 – Figure 1 Percent change in lumber spine BMD from baseline to month 12 by individual subjectResults7180 subjects were included in the study (Romo, n=3589; Pbo, n=3591). At month 12, the mean change from baseline in LS BMD T-score was 0.88 for Romo and 0.03 for Pbo. At month 24 (after both treatment groups received DMAb in the second year) mean increases in LS BMD T-score were 1.11 for Romo/DMAb and 0.38 for Pbo/DMAb. At month 12, the mean changes in TH BMD T-score were 0.32 for Romo and 0.01 for Pbo. At month 24, mean changes in TH BMD T-score were 0.45 for Romo/DMAb and 0.17 for Pbo/DMAb. In the Romo group, 99% of subjects showed an increase in LS BMD at month 12, with 89% achieving ≥6% gains (figure 1). Administration of Romo during the first year led to reductions versus Pbo in the relative risk of fractures during the second year, despite both groups receiving DMAb in the second year (reductions of 81% for vertebral fractures [p<0.001]; 32% for clinical fractures [p=0.052]; 39% for major osteoporotic fractures [p=0.034]).ConclusionsRomo versus Pbo resulted in substantially higher BMD T-score increases after one year. After transition to DMAb, BMD gains in both treatment groups were similar in the second year. One year of Romo treatment, followed by transition to DMAb, resulted in unprecedented gains in BMD and substantially reduced fracture rates during the second year even though subjects in both groups received DMAb. These data support the clinical benefit of rebuilding the skeletal foundation with Romo treatment before transition to DMAb.Reference[1] Cosman F, et al. N Engl J Med2016;375:1532–43.AcknowledgementsFunding: Amgen Inc., UCB Pharma, and Astellas PharmaDisclosure of InterestF. Cosman Grant/research support from: Amgen Inc.; Eli Lilly; Radius, Consultant for: Amgen Inc.; Eli Lilly; Radius, Speakers bureau: Amgen Inc.; Eli Lilly; Radius, D. B. Crittenden Shareholder of: Amgen Inc., Employee of: Amgen Inc., S. Ferrari Grant/research support from: Amgen Inc.; UCB Pharma; MSD: Labatec, Consultant for: Amgen Inc.; UCB Pharma; AgNovos, Speakers bureau: Amgen Inc.; UCB Pharma; AgNovos, A. Khan Grant/research support from: Amgen Inc; Alexion; Shire, Consultant for: Amgen Inc.; Eli Lilly, Speakers bureau: Amgen Inc.; Eli Lilly, N. E. Lane Grant/research support from: Amgen Inc., (Investigator on the FRAME study), Speakers bureau: Amgen Inc., K. Lippuner: None declared, T. Matsumoto Grant/research support from: Daiichi-Sankyo; Astellas Pharma, Consultant for: Chugai Pharmaceutical; Teijin Pharma; Ono Pharmaceutical, Speakers bureau: Chugai Pharmaceutical; Teijin Pharma; Ono Pharmaceutical, C. E. Milmont Shareholder of: Amgen Inc., Employee of: Amgen Inc., C. Libanati Shareholder of: UCB Pharma, Employee of: UCB Pharma, A. Grauer Shareholder of: Amgen Inc., Employee of: Amgen Inc.